2003
DOI: 10.1161/01.hyp.0000100424.84889.f7
|View full text |Cite
|
Sign up to set email alerts
|

Adiposity Is Related to Gender Differences in Impaired Stress-Induced Pressure Natriuresis

Abstract: Abstract-The purpose of this study was to determine if there are gender differences in stress-induced pressure natriuresis and to examine the effects of adiposity on these differences. The subjects were 151 boys and 141 girls 15 to 18 years of age who underwent a 5-hour stress protocol (2-hour prestress, 1-hour stress, 2-hour poststress) after being brought into similar levels of sodium balance. The gender-by-condition interaction was significant for systolic and diastolic blood pressure (Pϭ0.001 for both), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…Previously, our group, led by Harshfield, developed a theoretical model and protocol to study the impact of stress on sodium handling in the hypertensive process by examining the pressure natriuresis response to a period of extended competitive stress [30,31]. Using this model, impaired stress-induced pressure natriuresis (SIPN) is defined as an increase in BP during a period of extended stress without an adequate compensatory increase in urinary sodium excretion (U Na V) to contribute to the return of BP to pre-stress levels-that is, homeostasis.…”
Section: Salt Sensitivitymentioning
confidence: 99%
“…Previously, our group, led by Harshfield, developed a theoretical model and protocol to study the impact of stress on sodium handling in the hypertensive process by examining the pressure natriuresis response to a period of extended competitive stress [30,31]. Using this model, impaired stress-induced pressure natriuresis (SIPN) is defined as an increase in BP during a period of extended stress without an adequate compensatory increase in urinary sodium excretion (U Na V) to contribute to the return of BP to pre-stress levels-that is, homeostasis.…”
Section: Salt Sensitivitymentioning
confidence: 99%
“…We did not observe changes in adrenocorticotropic hormone, or in relationships between adrenocorticotropic hormone and sodium excretion during stress in our initial study on adults [7]. In addition, we did not observe an association between changes in insulin and sodium retention throughout our protocol [15,16]. …”
Section: Genetic Predispositionmentioning
confidence: 70%
“…Percent of body fat independently accounted for 4.6% of the variance of the stress-induced change in sodium excretion and 11.2% of the variance of sodium excretion during stress. In our third study on 151 boys and 141 girls, Harshfi eld et al [15] reported that body mass index was inversely related to sodium excretion during the stress period in boys. The magnitude of the correlation became greater when considering only boys with a body mass index greater than 25.…”
Section: Adipositymentioning
confidence: 75%
See 2 more Smart Citations